Inhibitory effect of infliximab on orthodontic tooth movement in male rats. (December 2022) - Fu, Chaoran; Gan, Lei; Yang, Benyi; Wu, Yilin; Meng, Bowen; Wu, Dongle; Zheng, Jinxuan; Cao, Yang
Abstract: Objective: This study aimed to investigate the effect of infliximab on orthodontic tooth movement in rats. Materials and methods: Sixty male Sprague-Dawley rats were randomly divided into two groups: saline group and infliximab group. The two groups of rats received weekly intraperitoneally injection of saline or infliximab (5 mg/kg), respectively. After four weeks of injection, five rats in each group were euthanized and orthodontic appliances were placed in the other twenty-five rats each. On days 1, 3, 7, 14 and 21, five rats from each group were euthanised. Maxillae of all the rats were collected and examined by micro-computed tomography, haematoxylin and eosin staining, tartrate-resistant acid phosphatase staining, and immunohistochemical staining of tumour necrosis factor (TNF)-α, receptor activator of nuclear factor κB ligand (RANKL), receptor activator of nuclear factor κB (RANK), and osteoprotegerin (OPG). All data were analysed with Mann-Whitney test. Results: Infliximab inhibited orthodontic tooth movement and decreased osteoclastogenesis on the compression side during orthodontic tooth movement. The elevated TNFα level, induced by orthodontic force, was decreased by infliximab. Furthermore, infliximab reduced the expression of RANKL and RANK, while increased the expression of OPG on the compression side. Conclusion: Infliximab inhibits orthodontic tooth movement by reducing levels of TNF-α, RANKL, and RANK, while increasing level of OPG, and decreasing osteoclastogenesis on the compression side of periodontium. Highlights: Infliximab slows down orthodontic tooth movement in rats. Infliximab inhibits osteoclast formation in periodontium during tooth movement. Infliximab reduces TNFα on the compression side of orthodontic tooth movement. Infliximab may function by inhibiting RANKL/RANK pathway.